The effects of slow- and fast-rhythm classical music on progressive cycling to voluntary physical exhaustion. - Szabo A; Small A; Leigh M (Journal of Sports Medicine & Physical Fitness, 1999)
BACKGROUND: To investigate, based on the parallel information processing model and arousal hypothesis, whether musical tempo and its manipulation during exercise affect the maximal workload (watts) achieved during progressive cycling. METHODS: Design: repeated measures experiment that involved one control and four treatment conditions. Settings: the experiment was performed in a controlled laboratory environment. Participants: twenty-four male and female volunteers, recruited from among a University population, were tested. Intervention: the data collection proceeded in five counterbalanced test-sessions that included control (C), slow music (SM), fast music (FM) slow to fast music (SFM) and fast to slow music (FSM) interventions. In the last two conditions, musical tempo was changed when the participant's maximal HR reserve has reached 70%. In all test-sessions, participants started to cycle at 50 watts and then the workload was increased in increments of 25 watts every minute until self-declared exhaustion. Maximal ergometer cycling was defined as the workload at the last completed minute of exercise. Measures: workload, HR, and postexperimental ratings of test-session preferences were the dependent measures. RESULTS: Significantly higher workload was accomplished in the SFM condition. No between-session differences were seen in HR. The results also yielded significantly better 'efficiency', in terms of workload/HR reserve ratio, in the SFM session. Participants preferred the FM and SFM sessions more than the other sessions. CONCLUSIONS: Switching to FM during progressive exercise results in the accomplishment of more work without proportional changes in HR. These effects may be due to distraction from fatigue and are, apparently, dependent on the attention capturing strength of the distracting stimulus.